1998
DOI: 10.1101/gad.12.2.175
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr interacts with the nuclear transport pathway to promote macrophage infection

Abstract: HIV-1 Vpr promotes nuclear entry of viral nucleic acids in nondividing macrophages and also causes a G 2 cell-cycle arrest. Consistent with its role in nuclear transport, we show Vpr localizes to the nuclear envelope in both human and yeast cells. Like the importin-␤ subunit of the nuclear import receptor, Vpr also interacts with the yeast importin-␣ subunit and nucleoporins. Moreover, overexpression of either Vpr or importin-␤ in yeast blocks nuclear transport of mRNAs. A mutant form of Vpr (Vpr F34I) that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
336
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(372 citation statements)
references
References 58 publications
30
336
6
Order By: Relevance
“…The third viral protein involved in nuclear import of HIV-1 PIC is the viral protein R (Vpr) (Heinzinger et al, 1994;Popov et al, 1998) which is present only in lentiviruses. Vpr contains two non-canonical NLS that may contribute to nuclear transport of the PIC (Jenkins et al, 1998), and interacts with cellular import machinery through importin  and the nucleoporins (Popov et al, 1998;Vodicka et al, 1998). A study based on the overexpression of Vpr has suggested that PIC enters the nucleus by inducing herniations and partial breaking of the nuclear envelope ).…”
Section: Nuclear Importmentioning
confidence: 99%
See 1 more Smart Citation
“…The third viral protein involved in nuclear import of HIV-1 PIC is the viral protein R (Vpr) (Heinzinger et al, 1994;Popov et al, 1998) which is present only in lentiviruses. Vpr contains two non-canonical NLS that may contribute to nuclear transport of the PIC (Jenkins et al, 1998), and interacts with cellular import machinery through importin  and the nucleoporins (Popov et al, 1998;Vodicka et al, 1998). A study based on the overexpression of Vpr has suggested that PIC enters the nucleus by inducing herniations and partial breaking of the nuclear envelope ).…”
Section: Nuclear Importmentioning
confidence: 99%
“…The cellular machinery required for the nuclear import of proteins is also involved in HIV-1 PIC import (Fouchier et al, 1998;Gallay et al, 1997;Gallay et al, 1996;Vodicka et al, 1998). However, it is not clear whether nuclear import receptors (karyopherins or importins) are required for the nuclear transport of IN: the nuclear accumulation of IN has been shown to be independent of importins and of the associated GTPase Ran activity (Depienne et al, 2001) Finally, nuclear import and integration of HIV-1 vectors can also occur independently of mitosis in cycling cells (HeLa) (Katz et al, 2003).…”
Section: Nuclear Importmentioning
confidence: 99%
“…Prior to the suggestion of this nucleotide-level, cis-acting mechanism, peptide signals in HIV-1 MA [127][128][129][130][131][132][133][134][135], IN [132,136] and Vpr [100,130,[137][138][139][140] were implicated in signal-mediated transport of the preintegration complex through the nuclear pore (reviewed in [98,99,101,141]). Some functional assignments to proteins have also been contested [142][143][144][145] and the whole area of the mechanism of nuclear import is regarded as unsettled at present; for current summaries of these controversies, see [99,102].…”
Section: Mechanisms Of Lentiviral Nuclear Import: Central Dna Flaps Amentioning
confidence: 99%
“…Experiments in macrophages strongly suggest an important role for Vpr in mediating the nuclear import of HIV-1 PICs into the nucleus of nondividing cells [20]. The mechanism of Vpr-mediated nuclear import is not clear, it is likely that Vpr interacts directly or indirectly with cellular machinery regulating the nucleo-cytoplasmic shuttling [21][22][23][24][25].…”
Section: Viral Protein R (Vpr)mentioning
confidence: 99%
“…However, other reports do not fit this hypothesis. Vpr was shown to locate predominantly in the nucleus or at the nuclear membrane [25,53,54], but not in the mitochondria. In addition, it has been reported that Vpr activates caspase-8 [55,56] which should not be activated in the intrinsic MOMP pathway.…”
Section: Viral Protein R (Vpr)mentioning
confidence: 99%